Analisis Economic Value Added (Eva) Dan Market Value Added (Mva) Terhadap Kinerja Keuangan Pada Perusahaan Telekomunikasi Di Bei 2017-2022 - Anwar , Anas Iswanto; Randy , Muh. Fuad; Irwin , Muh.; Putri , Ratih Astiakurnia (Bata Ilyas Educational Management Review, 2022)
This study is aimed to determine whether EVA and MVA affect the financial performance of telecommunications companies listed on IDX in 2017-2020. This study used quantitative methods. Data collection techniques in this study used library research and field research. The population in this study were all telecommunication companies and the data analysis tools used were multiple linear regression analysis, t- test and F-test. The results showed that EVA had no effect on financial performance. However, different results were shown by MVA, it effected on the financial performance of telecommunications companies based on the results of t-test. The f- test results showed that Economic Value Added (EVA) had no effect on financial performance and MVA effected on Financial Performance in simultaneously analysis.